2013
DOI: 10.1371/journal.pone.0056366
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of ZDHHC2 Is Associated with Lymph Node Metastasis and Poor Prognosis in Gastric Adenocarcinoma

Abstract: BackgroundZinc finger, DHHC-type containing 2 (ZDHHC2), originally named as reduced expression associated with metastasis protein (REAM), has been proposed as a putative tumor/metastasis suppressor gene and is often aberrantly decreased in human cancers. However ZDHHC2 expression pattern and its clinical significance have not yet been investigated in gastric adenocarcinoma.Methodology/Principal FindingsQuantitative Real-Time PCR (qRT-PCR) and immunostaining were performed to detect ZDHHC2 expression in gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…There are several potential mechanisms supporting this phenomenon, including Snail-dependent reduction in DHHC protein acyl transferase activity, increased expression or activity of acyl protein thioesterases, or reduction in palmitoyl-CoA levels. Several DHHC enzymes are reported to safeguard cells from malignancy, including DHHC2, DHHC14, and DHHC17 3739 , altering the membrane organization and localization of key signaling proteins. This repression is unlikely due to redox regulation of DHHC activity, since we report Snail expression leads to a broad induction of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…There are several potential mechanisms supporting this phenomenon, including Snail-dependent reduction in DHHC protein acyl transferase activity, increased expression or activity of acyl protein thioesterases, or reduction in palmitoyl-CoA levels. Several DHHC enzymes are reported to safeguard cells from malignancy, including DHHC2, DHHC14, and DHHC17 3739 , altering the membrane organization and localization of key signaling proteins. This repression is unlikely due to redox regulation of DHHC activity, since we report Snail expression leads to a broad induction of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that reduced ZDHHC2 expression is observed in gastric adenocarcinoma patients and associated with lymph node metastasis and independently predicts an unfavorable prognosis [28]. However, the expression level of ZDHHC2 in HCC remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…DHHC5 seems to have an oncogenic role that is dependent on its catalytic activity, contributing to tumor formation in NSCLC [40]. On the other hand, DHHC2 plays a putative tumor suppressor role as indicated by its reduced expression in gastric tumor tissues, which is associated with lymph node metastasis [41].…”
Section: Fatty Acyltransferases: Zdhhcs Nmts and Mboatsmentioning
confidence: 99%